The Use of Medical Grade Honey on Infected Chronic Diabetic Foot Ulcers-A Prospective Case-Control Study - Adéla Holubová; Lucie Chlupáčová; Jitka Krocová; Lada Cetlová; Linsey J. F. Peters; Niels A. J. Cremers; Andrea Pokorná (MDPI AG, 2023)
Non-healing wounds are usually colonised and contaminated by different types of bacteria. An alternative to antibiotic treatment in patients with infected wounds with local signs of inflammation may be medical grade honey (MGH). MGH has antioxidant, antimicrobial, anti-inflammatory, and immunomodulatory features. This study aims to evaluate the effect of MGH therapy on infected non-healing wounds, especially for diabetic foot syndrome. Prospective, observational case series (n = 5) of patients with wounds of diabetic foot syndrome are presented. There were five males with an average age of 61.6 years. All wounds were treated with MGH, and the healing trajectory was rigorously and objectively monitored. In all cases, there was a gradual disappearance of odour, pain, and exudation. Moreover, the wound areas significantly reduced within 40 days and there was a decrease in glycated haemoglobin and glycaemia values. All these outcomes resulted in improved quality of life of the patients. Despite bacterial colonisation, antibiotic treatment was not necessary. All wounds were completely healed. MGH has antimicrobial, anti-inflammatory, and antioxidant effects in diabetic foot syndrome wounds, does not increase glycated haemoglobin or glycaemia levels, and thus constitutes an effective alternative to the use of antibiotics in the treatment of locally infected wounds.